Speech at World Bank/IMF Annual Meetings Plenary, Washington, D.C., October 11, 2013 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the state of the global economy, and lessons drawn to the future of the World Bank Group. He mentioned strengthening Group financial discipline to become more efficient and to grow revenues. He promises that the World Bank Group will openly share our knowledge and experience with all 188 member countries, the private sector, and civil society. He wants to create a culture that retains the most motivated and talented people and attracts the best and brightest to the World Bank Group. He believes to chart a path toward universal financial access by bringing together multiple approaches and technologies. He promises to reduce transaction times by a third from conception of a project to first disbursement of funds. He concludes by saying that, working together with governments and development partners, have helped lift hundreds of millions of people out of extreme poverty.